Failure Mode and Effect Analysis (FMEA), Fuzzy Failure Mode and Effect Analysis (Fuzzy FMEA): A Case Study at Furniture Company - Karakuzu, Naciye; Karadağ, Seda; İnce, Nilgün (Fırat University, 2024)
Occupational health and safety (OHS) in Türkiye has become even more important with the law that came into force in 2012. In this context, businesses aim to prevent occupational accidents by identifying risky situations. Failures (dangerous situations) should be ranked according to their severity to have an effective precaution plan. With the failure mode effects and analysis (FMEA) technique, failures can be prevented before they occur. In this method, it is determined which failures should be prevented primarily according to the risk priority numbers (RPN) determined for each failure, and an error prevention plan is created accordingly. In this study, operational risk assessment dataset is utilized to apply FMEA and fuzzy FMEA methods to assess potential risks in a furniture manufacturing company. The utilized data set includes hazardous situations determined by the OHS expert and the probability, severity and detection values determined for each hazardous situation. Within the scope of the study, equally weighted occurrence (probability of occurrence), severity, and detection parameters in the classical FMEA method, are fuzzified and the results of the two methods are compared. The importance of the fuzzy logic approach in making a more effective failure precaution plan has been discussed.

Türkiye’de iş sağlığı ve güvenliği (İSG) 2012 yılında yürürlüğe giren kanunla daha da önemli hale gelmiştir. Bu kapsamda işletmeler, riskli durumları belirleyerek iş kazalarının oluşmasını önlemeyi amaçlamaktadır. Hataların (tehlikeli durumların) önem derecesine göre sıralanması etkin önlem planının oluşturulması için önemlidir. Hata türü ve etkileri analizi (HTEA) tekniği ile hatalar henüz ortaya çıkmadan önlenebilmektedir. Bu yöntemde hatalar için belirlenen risk öncelik sayılarına (RÖS) göre hangi hataların öncelikli olarak önlenmesi gerektiği belirlenmekte ve buna bağlı olarak da hata önleme planı oluşturulmaktadır. Bu çalışmada mobilya sektöründe faaliyet gösteren bir firmanın üretim operasyonlarından elde ettiği veri setleri kullanılarak HTEA ve bulanık HTEA yöntemleriyle risk analizi yapılmıştır. Kullanılan veri seti İSG uzmanı tarafından belirlenen tehlikeli durumlar ve her bir tehlikeli durum için belirlenen olasılık, şiddet ve tespit edilebilirlik (fark edilebilirlik) değerlerini içermektedir. Çalışma kapsamında, klasik HTEA yönteminde eşit olarak ağırlıklandırılan olasılık, şiddet ve ağırlık faktörlerinin Matlab programı kullanılarak bulanıklaştırılması sağlanmış ve iki yöntemin sonuçları kıyaslanmıştır. Daha etkin bir hata önleme planı hazırlamada bulanık mantık yaklaşımının önemi tartışılmıştır.
Hata Türü ve Etkileri Analizi (HTEA), Bulanık Hata Türü ve Etkileri Analizi (Bulanık HTEA): Mobilya Sektöründe Bir Uygulama
Keywords: Manufacturing Safety and Quality; İmalat Güvenliği ve Kalite